Carbon and nitrogen eroded from burned forests in the western U.S. - Pierson, Derek, author; Binkley, Daniel, advisor; Rhoades, Charles, committee member; Kelly, Eugene, committee member (Colorado State University. Libraries, 2013)
Post-wildfire landscapes and downstream aquatic resources are influenced by carbon (C) and nitrogen (N) losses from soil erosion. As opposed to soil erosion, rarely measured losses of sediment C and N may account for a substantial portion of fire impacts. We measured erosion of C and N following eight wildfires for four to six years in the western U.S and compared losses from untreated, burned hillslopes and small catchments with those from adjacent areas that received erosion mitigation treatments. Losses of C, N and sediment were greatest the first two years and declined in subsequent years. Cumulative losses from untreated, burned areas were 16 - 4,700 kg C/ha and 0.7 - 185 kg N/ha over the study period. Across wildfire locations, median sediment C and N concentrations ranged from 0.011 - 0.036 g N/kg and 0.23 - 0.98 g C/kg. Post-fire erosion control treatments reduced C, N and sediment losses by 65-75% compared to untreated areas and generally increased the concentrations of C and N in eroded material. The total C and N lost in post-fire erosion was < 20% of the estimated amount lost from organic and mineral soil layers during combustion and < 5% of the estimated amount remaining in mineral soils after combustion. In general, the N lost with soil erosion is unlikely to impair the productivity of recovering forests, but the eroded N may have consequences on downstream water quality and aquatic habitat.
Keywords: carbon; erosion; hillslope; nitrogen; watershed; wildfire